TCM syndrome classification of patients with chronic kidney disease and its relationship with CKD staging - Leong, Shan Ying (Nanyang Technological University, 2020)
Chronic Kidney Disease (CKD) prevalence rates have been an upsurge in recent years. Despite treatments being continuously developed, CKD remains one of the top causes of death. In Singapore, Traditional Chinese Medicine (TCM) is regularly sought as an alternative treatment option. Thus, this paper aims to identify the common TCM syndromes of CKD patients and to correlate these syndromes to CKD staging. Data of 144 patients were collected from electronic medical database, using a data collection form crafted by physicians from STCMI’s Renal Special Clinic. The study showed that majority of the patients were Chinese, male, of older age with early CKD stages and comorbidities such as hypertension, hyperlipidemia, and diabetes mellitus. For TCM syndromes distribution, Spleen-Kidney Qi deficient syndrome (SKQD) existed in all CKD stages, especially in the early stages, while Spleen-Kidney Yang deficient syndrome (SKYD) was mostly observed in patients diagnosed with CKD 5. This study has provided an understanding of the relationship between TCM syndromes and CKD staging but more findings are required to bridge TCM and its scientific evidence for better CKD management.